Appropriate guidelines of Waste Management for Keudchang Sub-district, Maetang District, Chiangmai province, Thailand - Sawetrattanakul, S; Jansri, S. N.; Tantranont, N; Setthapun, W (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
Waste management is one of the major problems around the world. Governments and global organizations are starting to pay attention to the amount of waste left behind. Thai government drafted the National policies of waste management to manage waste in sustainable ways. Keudchang Sub-district confronts waste management problems due to the increase in the amount of waste, insufficient area for disposal, roadside and riverside litters, an illegal dump of rubbish in forests, and air pollution from waste incineration. The purposes of this research were to study the amount of waste and waste composition in 8 villages of Keudchang Community (KC), and develop appropriate guidelines of waste management. This participatory research collects data from both primary and secondary sources. Primary data sources include interviews and set up a public hearing stage with stakeholders in KC. Secondary data include a documentary of community context, meeting minutes, and other related documents. Qualitative data were analyzed with the content analysis method. The results showed that the KC produce an average of waste to 4,062.02 kg/day. These wastes could be classified into 4 types including organic waste (45.83%), recycle waste (28.01%), general waste (15.55%), and hazardous waste (10.60%) respectively. An individual person at KC produces an average of waste at 0.98 kg/day. Additionally, the results from conducting a public hearing stage of 8 villages revealed community awareness and solutions for waste management. All people in KC need to sort their wastes properly before disposal in 4 ways. First, organic waste. Each household needs to dig a hole and dump the organic wastes into it. The organic wastes should be managed and separated from other wastes. Second, recycle waste. Various approaches to recycle waste include waste credit bank (WCB), waste volunteer, monthly fee, and self-management. The WCB would be a hub for the communities to make profits and reduce landfill wastes. A waste volunteer would be a volunteer person who buys community wastes and sell them to outsiders. The monthly fee would be an approach where each household pays 70 baht/month to a garbage collector. Self-management would be another approach where households sort out, eliminate, sell, and manage wastes by themselves. Third, general waste. General waste could be divided into 2 groups as profitable waste and community dumping ground. Profitable waste could be sold to WCB or waste stores by each household. Community dumping ground would be an area allocated to all households for waste disposal. All households would not allow to throw garbage or wastes into other areas, but community dumping ground. Finally, hazardous waste. Hazardous waste would need to dispose of carefully in the trash can located at the office of the village headman. The findings from this study suggested setting up a waste management committee (WMC), as well as defining their roles and responsibilities. Local administrative organizations and community leaders also need to support, supervise, and control community waste management for resource-efficient and sustainable societies